Signal space concept for digital communication simulation - Tay, Wen Wei (2019)
This report focuses on the research of signal space concepts for digital communication systems with MATLAB simulations. As the existing signal space still has errors after the transmission of the data, further research is required on the different signal spaces to minimize the probability of the errors. The channel that will be focused will be on additive white Gaussian noise (AWGN), which is a common statistically random radio noise with the use of different modulation schemes. The different modulation schemes like M-ary phase shift keying (M-PSK) and M-ary quadrature amplitude modulation (M-QAM) of various signal spaces will be tested over this AWGN channel. The larger the signal space, the higher bit error rate will be obtained due to the faster data rate transmission. We will further explore each of the modulation techniques and slowly expand the signal space to analyse different performance results with bit-error rate and symbol-error rate performance.